Fascinating Autonomous ROBOT for Calamity Strategies That Can Offer Assistance under Rubble and to Total Errands Rapidly and Proficiently - Farhin Farhad Riya, Kazi Sultana Farhana Azam (International Journal of Advanced Science and Technology, 2020)
Within the normal catastrophe robots are utilized to look casualties and survivors. Autonomous robot is the robot that has been outlined for the purpose of protecting individuals, because It can get to inaccessible areas. In this paper, Arduino and Sensors based system for rescuing human along with six various kinds of sensors, Ultrasonic Sensor, Flaming Sensor, PIR Sensor, Wireless Sensor, DHT11 Temperature & Humidity Sensor, MQ135 Gas Sensor, Servo Motor, Bluetooth Module, IP Cam, and a microphone, is proposed. Ultrasonic sensor is used for autonomous and its task is to find nearby obstacles, generates sound wave, taking reading and passes it to the servo motor. Then the servo motor turns around at 180-degree angle and searches for in left and right direction. Flaming Sensor is used for sensing fire direction. We have used Temperature and Humidity Sensor for measuring temperature and humidity because victim can be dehydrated that enhances the chances for causing death. As the volume of gas increases, the likelihood of fire is increased. For this reason, gas sensor is used to measure the quantity of specific gases. Bluetooth module is used for transmitting the readings from all the sensors to the app, IP cam is used for live streaming, light controlling, photo snap, video record, duel communication with victim using microphone. The purpose of utilizing the PIR sensor is for detecting human. The intention for using Wireless sensor module is to hold network under the rubble or in any constructions. We have used batteries in a series connection for supplying power. When we have performed the proposed design system in practical phase we have encountered a 96.42 % average accuracy level. Our proposed system introduces the design of a robotic system with low-cost and the performance of controlling the rescue system under the rubble or in any constructions during natural disaster.